Burnout syndrome, doctor-patient relationship and family support of pediatric medical staff during a COVID-19 Local outbreak in Shanghai China: A cross-sectional survey study - Lyu, Baiyu; Xu, Meijia; Lu, Lijuan; Zhang, Xiaoying (Frontiers in Pediatrics, 2023)
Objectives: To explore burnout syndrome (BOS) incidence, doctor-patient relationship, and family support on pediatric medical staff in Shanghai comprehensive hospitals during a COVID-19 local outbreak. Methods: A cross-sectional survey of pediatric medical staff from 7 comprehensive hospitals across Shanghai was conducted from March to July 2022. The survey included BOS, doctor-patient relationships, family support, and the related factors of COVID-19. The T-test, variance, the LSD-t test, Pearson's r correlation coefficient, and multiple regression analyses examined the data. Results: Using Maslach Burnout Inventory-General Survey（MBI-GS）, 81.67% of pediatric medical staff had moderate BOS, and 13.75% were severe. The difficult doctor-patient relationship was positively correlated with emotional exhaustion(EE), cynicism(Cy), and negatively with personal accomplishment(PA). When medical staff need help, the greater the support provided by the family, the lower the EE and CY, and the higher the PA. Conclusion: The severe BOS of pediatric medical staff in Shanghai comprehensive hospitals during a COVID-19 local outbreak. We provided the potential steps that can be taken to reduce the increasing rate of BOS in pandemics.